Perception of risk as a mediator between personality and perception of health: test of a model. (2023)
This research article addresses the relationships among personality, risk perception, and health perception. The personality construct has been one of the main topics of research in psychology throughout history and is understood as the set of traits or cognitive, affective and behavioral characteristics that an individual possesses. Important relationships have been found that show the impact of personality on people's health as well as the impact of health conditions on the configuration of personality. This research investigates the perception of risk as a mediating trait between personality and perception of health.